Thermal conductivity of lightweight concrete depending on the moisture content of the material - Shukurov, Gayrat; Mamarajabovich, Musaev Sharof; Turakulovna, Egamova Marguba; Mamasolievna, Xajimatova Mavludahon (International Journal of Psychosocial Rehabilitation, 2020)
This article presents the results of theoretical and laboratory field thermophysical studies and defines the thermal conductivity coefficients of lightweight concrete. Using the “FEITRON” device, we studied the dependence of the thermal conductivity coefficient of expanded clay concrete on moisture according to the method based on the stationary thermal regime developed at the Moscow Scientific Research Institute of Building Physics on plate samples measuring 25x25x5 cm. At the same time, five degrees of moisture were selected for the concrete in the humidity range from absolutely dry to 2, 5, 10, and 15% humidity in the range of expanded clay concrete densities from 700 to 1300 kg/m3. In addition, with the help of the “ИТС-1” device, a thermal conductivity meter, studies were conducted to determine the dependence of the coefficient of thermal conductivity of foam concrete on the moisture content of the material. The “ИТС-1” device is designed to measure the thermal conductivity and thermal resistance of building and heat-insulating materials using the stationary heat flux method in accordance with GOST 7976-99. The studies were conducted according to the method developed by representatives in Moscow (НИИЖБ) and St. Petersburg. The principle of operation of the device is based on the creation of a stationary heat flux passing through the studied flat sample. Expanded clay samples with a density of 700 to 1300 kg / m3 and foam concrete blocks with a density of 600 - 700 kg / m3 from local raw materials were made to determine the heat transfer coefficient depending on the moisture content of the material. As a result of the research, empirical formulas were proposed for determining the thermal conductivity of expanded clay concrete with a density of 700, 740, 900, 1050 and 1300 kg / m3 and foam concrete blocks with a density of 600–700 kg / m3 depending on the moisture content of the material.